Optimizing the function of the library as a public service facility - Ervan Kus Indarto, Koko Srimulyo, Helmy Prasetyo Yuwinanto, Menia Prayesti Kurniasari, (Opción, 2019)
This study aims to investigate optimizing the function of the library as a public service facility at East Java via a descriptive explanative method using qualitative and quantitative approaches. As a result, budget constraints, quantity, and quality of human resources serve as obstacles in maximizing the function of the library as a public service provider in order to improve culture and reading interest in the community. In conclusion, public regional library as one of the public service facilities is expected to be able to provide and fulfill the general information needs of the society in order to increase their knowledge.